2017
DOI: 10.3389/fpls.2017.00481
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Population Genomics of Forsythia (Forsythia suspensa) Reveal That Ecological Habitats Determine the Adaptive Evolution of Species

Abstract: Understanding the genetic mechanisms of adaptation to environmental variables is a key concern in molecular ecology and evolutionary biology. Determining the adaptive evolutionary direction and evaluating the adaptation status of species can improve our understanding of these mechanisms. In this study, we sampled 20 populations of Forsythia suspensa to infer the relationship between environmental variables and adaptive genetic variations. Population structure analysis revealed that four genetic groups of F. su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…The genetic structure of species is affected by the interaction of multiple factors, such as the transmission model of seeds and pollen, population demographic history, geological events, geographical or ecological barriers and divergent selection of environmental factors (Yang et al, 2017;Ohsawa & Ide, 2008). While a strong gene flow (N m > 1) may weaken the segregation of species, the hierarchical structure of P. juncea revealed by AFLPs here could scarcely be ascribed to gene drift or inbreeding (Sui et al, 2009;Clark, Wentworth & O'Malley, 2000;Slatkin, 1993).…”
Section: Geographical Barriers and Local Adaptation Lead To Spatial Gmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic structure of species is affected by the interaction of multiple factors, such as the transmission model of seeds and pollen, population demographic history, geological events, geographical or ecological barriers and divergent selection of environmental factors (Yang et al, 2017;Ohsawa & Ide, 2008). While a strong gene flow (N m > 1) may weaken the segregation of species, the hierarchical structure of P. juncea revealed by AFLPs here could scarcely be ascribed to gene drift or inbreeding (Sui et al, 2009;Clark, Wentworth & O'Malley, 2000;Slatkin, 1993).…”
Section: Geographical Barriers and Local Adaptation Lead To Spatial Gmentioning
confidence: 99%
“…To conserve and exploit the genetic resources of plants scientifically, a detailed acquaintance of the distribution and amount of genetic variability within the organism is demanded, mainly focused on the investigation of the population genetic diversity and hierarchical structure (Feng, Jiang & Fan, 2015;Costa et al, 2016). A heavily researched subject in evolutionary biology and molecular ecology is the investigation of the genetic basis of local adaptation in non-model species in natural plant populations (Di Pierro et al, 2017;Yang et al, 2017). Adaptive divergence driven by seasonal climate change and habitat heterogeneity can result in local adaptation (Yang et al, 2017;Hedrick, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most non-model species do not have established genomic information to appropriately place sufficient markers across the genome. Therefore, two characteristics, i.e., no requirement for a priori genome knowledge and a high covering density in genomes, are indispensable for the use of these molecular markers in landscape genomics ( Yang et al, 2017 ).…”
Section: Molecular Markers In Landscape Genomicsmentioning
confidence: 99%
“…The typical regional vegetation consists of deciduous broadleaved forest (DBLF). To date, only two landscape genetics studies of Cotinus coggygria and Forsythia suspensa in this region have been reported (Lei et al 2015;Yang et al 2017). However, these informations are insuicient to understand the adaptive evolution of regional vegetation.…”
Section: Introductionmentioning
confidence: 99%